The Influence of Corporate Governance Mechanisms on Earnings Management and Earnings Volatility in The Indonesian Banking Sector - Prisila Damayanty; Pintor S. Shine Patiro; Hendi Prihanto (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effects of corporate governance mechanisms on earnings management and on earnings volatility in the Indonesian banking sector. The corporate governance variables examined include managerial ownership, institutional ownership, audit committee independence, audit quality, and the frequency of audit committee meetings. This study employs a quantitative approach using secondary data from audited financial statements of banking companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The sample consists of 39 companies selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that corporate governance mechanisms significantly affect earnings management, with the frequency of audit committee meetings being the most dominant variable. In addition, earnings management has a significant positive effect on earnings volatility. This study strengthens agency theory and positive accounting theory by showing that corporate governance serves as a monitoring mechanism that reduces earnings management in the banking industry. The findings have implications for banks, regulators, investors, and academics in improving supervisory effectiveness and the quality of financial reporting.